2020
DOI: 10.1002/berj.3635
|View full text |Cite
|
Sign up to set email alerts
|

What PISA and ASPIRES studies tell us about the nuanced influence of cultural capital on student learning: Construct complexity, student outcomes and contexts

Abstract: This article juxtaposes the evolving scholarship investigating the influence of cultural capital on student learning and the developing trajectory of sociologists employing quantitative research methods. It critically reviews results from 34 studies analysing PISA or ASPIRES data to generate three key insights demonstrating complexities in relationships between cultural capital and student outcomes. First, cultural capital is a complex construct with many variables (different forms of cultural capital, highbro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…This study found that family cultural capital had a significant effect on high school students' academic achievement, thus validating the relevant findings of previous studies [18,36,42]. We discovered a high intergenerational transfer of cultural capital.…”
Section: The Influence Of Family Cultural Capital On Students' Academ...supporting
confidence: 91%
See 1 more Smart Citation
“…This study found that family cultural capital had a significant effect on high school students' academic achievement, thus validating the relevant findings of previous studies [18,36,42]. We discovered a high intergenerational transfer of cultural capital.…”
Section: The Influence Of Family Cultural Capital On Students' Academ...supporting
confidence: 91%
“…Tan [36] implied that embodied cultural capital played a more important role than other cultural capitals. Embodied cultural capital mainly includes highbrow cultural capital.…”
Section: The Embodied Statementioning
confidence: 99%
“…Therefore, cultural capital has a more significant impact on the success of student education [64]. According to Tan, the influence is very large in an education system that does not receive government support and there are gaps in developing countries [93]. Meanwhile, the social and cultural capital provided by NGO, extended families and communities for education helps achieve a bachelor's degree, and it has not affected the student's academic performance in college.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural capital, which can be passed from one generation to another, presents itself in three dimensions -"as embodied (dispositions and practices), institutionalised (educational qualifications), and objectified (cultural goods)" (Willekens & Lievens, 2014, p.98). Consequently, different scholars have, over the years, assessed the links between cultural capital and students' learning and academic achievement (Aswathi, 2019;Breinholt & Jaeger, 2020;Maunah, 2020;Tan, 2020).…”
Section: Studies On Family Inputsmentioning
confidence: 99%